Analisis Wacana Kritis Teun A. Van Dijk Atas Konstruksi Realitas Pendidikan dalam Media Massa - Sitorus, Novellyn Debora; Sinaga, Cristine Fitta Homasan; Sihombing, Berliana (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2026)
This study aims to examine the construction of educational reality in the Tempo article entitled “Sekolah Tanpa Beban untuk Generasi Cerdas dan Berdaya Saing” by applying the Critical Discourse Analysis model of Teun A. van Dijk. The research employs a descriptive qualitative approach, with the data source consisting of an online media article published by Tempo. Data were collected through documentation and note-taking techniques, and subsequently analyzed based on three levels of discourse structure: macrostructure, superstructure, and microstructure. The findings indicate that at the macrostructural level, the text constructs a central theme concerning limited access to education in the Maluku Utara archipelago and consistently associates it with the role of the local government as the primary solution provider. At the superstructural level, the article is organized in a feature format following a personal narrative, policy, expectation pattern, which functions to build empathy while simultaneously legitimizing the “education without burden” policy. At the microstructural level, lexical choices, the use of metaphors, the dominance of active sentences, and the emphasis on quantitative data strengthen the image of the government as a responsive actor and naturalize the ideology of education as a fundamental right that must be guaranteed by the state. This study affirms that media texts not only convey information but also shape readers’ perspectives through structured and ideological discursive strategies. The findings contribute to the development of media linguistics studies and the strengthening of critical literacy in language education.